Self-reported level of and factors influencing the compliance to desferrioxamine therapy in multitransfused thalassaemias - Lee, Way Seah; Toh, T.H.; Chai, P.F.; Soo, T.L. (Wiley, 2011)
Aim: To analyse the self-reported degree of and factors influencing the compliance to desferrioxamine (DFO) therapy in children with transfusion-dependent thalassaemia major in Malaysia. Methods: A cross-sectional study was conducted on all children with thalassaemia major on DFO attending Likas Hospital, Sabah, in September 2008. Patients or carer-providers were interviewed to report on the degree of compliance as either highly (administering >90 of DFO), moderately (51-90), poorly (1-50) or non-compliant (0) to DFO in the preceding month. The latest serum ferritin levels were noted. Results: The median (range) age at first blood transfusion of these 139 (73 males, median (range) age at interview: 9.0 years (2-16 years)) patients were 1.0 year (2 months to 10 years). The median (range) duration of regular DFO therapy was 2 years (2 months to 10 years). Forty-three (31) of the patients reported themselves to be highly compliant, 70 (50) moderately and 26 (19) poorly or non-compliant. Multivariate analysis showed that a lower family income negatively affected the degree of compliance, while family support positively affected the degree of compliance to DFO. No correlation existed between self-reported degree of compliance and latest serum ferritin level (6444 +/- mu mol/L; P = 0.186). Conclusion: The self-reported compliance to DFO therapy was moderate in this cohort of patients with thalassaemia major in Malaysia. The serum ferritin level was high, possibly because of the relatively short duration of DFO therapy and compliance. Oral iron chelator should be considered to improve the compliance to iron chelation.